Changes in the Activity of Small Intestinal Enzymes under the Influence of Organophosphorus Pesticides - Askaryants V.P; Yunusov A.A; Babadjanova F.A (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Organophosphorus pesticides are widely used agricultural chemicals with known biological effects, yet their impact on digestive physiology remains incompletely understood. Specific Background: Previous research has demonstrated that chlorophos, an organophosphorus compound, suppresses intestinal enzyme activity in experimental animals, with lipase showing particular sensitivity, though comprehensive characterization of organophosphorus effects on small intestinal enzyme systems is lacking. Knowledge Gap: The detailed dose-dependent and time-dependent effects of butiphos, a commonly used organophosphorus pesticide, on the complete spectrum of intestinal digestive enzymes and the reversibility of these effects have not been systematically investigated. Aims: This study investigated the effects of acute and chronic butiphos exposure at varying doses on key small intestinal enzymes including monoglyceride lipase, glycyl-valine dipeptidase, invertase, alkaline phosphatase, and amylase in laboratory rats. Results: Monoglyceride lipase activity was consistently and profoundly suppressed (up to 9-fold reduction) across all exposure regimens, while other enzymes exhibited dose- and time-dependent wave-like fluctuations with transient increases or decreases followed by partial recovery; cessation of pesticide administration resulted in normalization of enzymatic activity and mucosal mass. Novelty: This research provides the first comprehensive characterization of butiphos-induced alterations in intestinal enzyme-forming function, revealing selective esterase inhibition and reversible enterocyte dysfunction. Implications: These findings highlight potential impairment of digestive efficiency during chronic organophosphorus pesticide exposure and underscore the high sensitivity of enterocyte enzymatic systems to these agricultural compounds.Keywords : Organophosphorus Pesticides, Intestinal Enzymes, Monoglyceride Lipase, Butiphos, Digestive FunctionHighlight : Monoglyceride lipase activity consistently suppressed regardless of butiphos dose or duration. Protein and carbohydrate enzymes showed wave-like fluctuations with partial recovery periods. Enzymatic activity and mucosal mass normalized after pesticide administration cessation.